Sistem Informasi Penjualan Berbasis Web di Toko Ajai Komputer Kota Barabai - Yen, Yenni; Pantjarani, Ari; Hamid, Abdul (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
The development of the increasingly advanced era is marked by all activities being able to be done digitally. The development of the digital era is also increasingly running so fast that it cannot be stopped by humans. The development of information technology has changed the way businesses operate, especially in sales and inventory management. Toko Ajai Komputer Barabai, as a representation of the retail sector, faces challenges in improving operational efficiency in sales and inventory management which has an impact on customer service. Manual methods that are often used in sales and inventory management are no longer effective in facing the demands of a rapidly growing market. The use of manual recording in books can cause information to be lost or misplaced. This study aims to build and develop a Web-Based Sales Information System specifically for Toko Ajai Komputer Kota Barabai with the integration of information technology to improve operational efficiency in the sales and inventory process. The system method uses the SDLC (System Development Life Cycle) Waterfall model to build and develop a Web-Based Sales Information System at Toko Ajai Komputer Kota Barabai. The Waterfall method has a structured and systematic approach, which involves needs analysis, system design, implementation, evaluation, and maintenance. The implementation of a web-based sales information system at Toko Ajai Komputer Barabai forms a transformation that increases operational efficiency, especially in the sales process which simplifies sales and inventory management.